Use of Waste Salmon Bones as a Biomaterial - Bas, Merve; Daglilar, Sibel; Kalkandelen, Cevriye; Gunduz, Oguzhan (IEEE, 2020)
In the presented study; Hydroxyapatite (HA) used in many areas such as filling of cavities, bone tissue treatments, chin-face, orthopedic and dental surgeries, was obtained from waste salmon fish bones. Instead of producing chemically in a laboratory environment, hard tissue waste of natural resources was used. As trace elements such as magnesium, zinc, and strontium in the structure of natural resources support bone formation, waste salmon fish bones, which are a natural source, were preferred as raw materials. Other advantages include being easy to access raw materials, cheap and environmentally friendly. HA was obtained from salmon hones by the thermal calcination method. The obtained pure salmon hydroxyapatites were sintered at different temperatures, and the effect of changing sintering temperature on the density, microhardness, compressive strength, and elasticity module in the material was investigated. Crystal phase analysis of salmon hydroxyapatite powder and thermal analysis up to a certain temperature were made. MTT cytotoxicity test was performed to measure whether the materials were toxic. This study has the potential to contribute to the development of biomaterial studies for bone repair.
Keywords: biomaterial; hydroxyapatite; mechanical properties; waste Salmon fish bones; MECHANICAL-PROPERTIES; Computer Science; Engineering